Large gap two-dimensional topological insulators with prominent Rashba effect in ethynyl functionalized Ⅲ-Bi Buckled-Honeycomb monolayers. (October 2021) - Wang, Yonghu; Lei, Shuangying; Wan, Neng; Yu, Hong; Chen, Jie
Abstract: Recently, two-dimensional topological insulators have attracted extensive attention because of their excellent electronic transport performance and easy integration into electronic devices. However, the small bandgap limits their room-temperature application. Based on first-principles calculations, we predict that the ethynyl functionalized GaBi/InBi monolayers are topological insulators with large bandgap ( E g = 0.512   e V ) and significant Rashba SOC effect ( α R = 2.819  eVÅ ). The topological phases, which originate from s-p x, y band inversion induced by chemical bonding, can be maintained within the large-range biaxial strain. Additionally, the h -BN is found to be an ideal substrate for the growth of these QSH insulators. These findings indicate that the ethynyl functionalized Ⅲ-Bi monolayers are expected to be candidate materials for spintronics and quantum computing. These findings indicate that the ethynyl functionalized Ⅲ-Bi monolayers are expected to be candidate materials for spintronics and quantum computing. Highlights: We predict that the ethynyl functionalized GaBi/InBi monolayers are topological insulators with large bandgap ( E g = 0.512  eV ) and significant Rashba SOC effect ( α R = 2.819  eVÅ ) . We research the strain engineering and explain the change in topology phase through evolution of orbitals. We study the significant Rashba SOC effect and the electric field impact. The h -BN is found to be an ideal substrate for the growth of these QSH insulators.